HUBUNGAN KETERAMPILAN HITUNG, PERSEPSI TENTANG KETERAMPILAN GURU, CARA BELAJAR DENGAN HASIL BELAJAR - Elok Muliani Musa; Teddy Rusman; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
this study aims to determine the relationship of arithmetic skills, students 'perceptions of teachers' teaching skills and learning how to learn the results of class XII IPS Bina Mulya Bandar Lampung in the Academic Year 2012/2013. The population in this study were all students of class XII Bina Mulya which amounts to 53 siswa.Untuk determine the sample size of the population used the Cochran. Samples in this study were is 47 students. To test the hypothesis first, second, and third using partial correlation, multiple linear regression. Based on the analysis obtained the following results. 1. There is a relationship with the arithmetic skills of accounting when the students' perception of teachers' teaching skills and learn how to be controlled. 2. There is a relationship of students 'perceptions of teachers' teaching skills by learning outcomes of accounting when the arithmetic skills and learn how to be controlled. 3. There is a learning relationship with the learning outcomes of accounting when the arithmetic skills and students 'perceptions of teachers' teaching skills are controlled. 4. There are arithmetic relations skills, students 'perceptions of teachers' teaching skills and learning how to learn accounting. Kata Kunci: keterampilan hitung, persepsi, belajar, hasil.